2008
DOI: 10.1007/s11010-008-9761-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor-related gene polymorphisms and prostate cancer risk in North Indian population

Abstract: The purpose of this study was to analyse the frequency and type of mutations in the coding region of androgen receptor (AR) and to determine the role of polymorphisms in the intron 1 of ERalpha, exon 5 of ERbeta, intron 7 of progesterone, exon 7 of the aromatase (CYP19) and exon 9 of VDR genes in the risk of prostate cancer. PCR-RFLP analysis of all above the genes was on 100 prostate cancer patients and an equal number of matching controls. The study also included PCR-SSCP analyses of exons 2-8 of AR gene. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…In several cancers it has been shown that exposure to higher than median vitamin D was able to completely overcome the risks. 12 The same mechanisms may also hold true for ESRD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In several cancers it has been shown that exposure to higher than median vitamin D was able to completely overcome the risks. 12 The same mechanisms may also hold true for ESRD.…”
Section: Discussionmentioning
confidence: 93%
“…There are some reports where this gene polymorphism has been investigated in different malignancies among the Indian population [10][11][12] ; however, there is no study on ESRD patients from India. Our results showed that Apa1, Fok1, and Bsm1 gene polymorphism may be one of the genetic risk factors for ESRD among north Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…In which the objects were Asian population in 12 articles; and one was not control study (Bid et al, 2005); two shared the prostate cancer cases (Jianhe et al, 2004a;Jianhe et al, 2004b), so we only chose one according to our exclusion criteria (Jianhe et al, 2004a). At last, 10 articles were included in Meta-analysis (Watanabe et al, 1999;Habuchi et al, 2000;Hamasaki et al, 2001;Hamasaki et al, 2002;Suzuki et al, 2003;Huang et al, 2004;Jianhe et al, 2004a;Chaimuangraj et al, 2006;Onsory et al, 2008;Bai et al, 2009), including 1141 cases and 1685 control. The basic information are shown in Table 1.…”
Section: Basic Informationmentioning
confidence: 99%
“…No deviation of HardyWeinberg equilibrium was found for the variant rs2234693 for any study. Of them, six reports found a significant association for the variant and prostate cancer risk while the others did not found such association (Suzuki et al, 2003;Low et al, 2006;Onsory et al, 2008;Gupta et al, 2010;Sissung et al, 2011;Safarinejad et al, 2012). From the meta-analysis, no significant association between the rs2234693 and prostate cancer risk was found with the pooled OR was 1.15 (95% CI = 0.97-1.39) under dominant genetic model (Figure 2a).…”
Section: Resultsmentioning
confidence: 93%
“…These results indicated that rs9340799 may be a risk factor for prostate cancer and it may acts as a dominant model. rs2234693 and the susceptibility of prostate cancer In total, 17 individual studies were identified in the literature search stage that have evaluated the association between the rs2234693 and prostate cancer (Modugno et al, 2001;Suzuki et al, 2003;Tanaka et al, 2003;Fukatsu et al, 2004;Hernandez et al, 2006;Low et al, 2006;Berndt et al, 2007;Cunningham et al, 2007;Kjaergaard et al, 2007;Onsory et al, 2008;Sobti et al, 2008;Beuten et al, 2009;Gupta et al, 2010;Sonoda et al, 2010;Sissung et al, 2011;Szendroi et al, 2011;Safarinejad et al, 2012). Two of them were excluded for overlapping studied populations (Hernandez et al, 2006;Sobti et al, 2008).…”
Section: Resultsmentioning
confidence: 99%